2021
DOI: 10.1038/s41591-021-01322-9
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion on global rollout of COVID-19 vaccines

Abstract: More broadly, understanding and potentially influencing public opinion will be important components of any strategies to combat COVID-19 and prevent future pandemics 10 . This global problem requires global solutions, and our survey indicates that the redistribution of some pre-purchased vaccines to countries most in need has public support. data availabilityData are available from the authors upon request.❐Editorial note: This article has been peer-reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 6 publications
6
34
0
Order By: Relevance
“… ‡‡ In related work that analyzes this 13-country survey, we also find what appears to be altruistic attitudes regarding vaccine allocations. It is interesting to note that we find that a majority of respondents from the developed economies in our sample expressed support for donating at least 10% of their vaccine supplies to countries in need ( 35 ). …”
mentioning
confidence: 83%
“… ‡‡ In related work that analyzes this 13-country survey, we also find what appears to be altruistic attitudes regarding vaccine allocations. It is interesting to note that we find that a majority of respondents from the developed economies in our sample expressed support for donating at least 10% of their vaccine supplies to countries in need ( 35 ). …”
mentioning
confidence: 83%
“…2 , 3 However, notwithstanding compelling arguments, the willingness of HIC governments to make sufficient COVID-19 vaccine doses available to LICs is likely to hinge largely on the extent to which the general public are supportive. In recent online survey work, we provided evidence of strong public support for donations to LICs that was consistent across seven HICs [ 12 ]. We documented evidence that, in each country, between 48% and 56% supported some level of donation of vaccine doses [ 12 ].…”
Section: Introductionmentioning
confidence: 95%
“…In recent online survey work, we provided evidence of strong public support for donations to LICs that was consistent across seven HICs [ 12 ]. We documented evidence that, in each country, between 48% and 56% supported some level of donation of vaccine doses [ 12 ]. Moreover, of those who supported vaccine donations, over 70% favoured donating at least 10% of their country’s doses [ 12 ].…”
Section: Introductionmentioning
confidence: 95%
“…The most comprehensive study on public opinion about the global rollout of COVID-19 vaccines 25 surveyed 8209 participants from Australia, Canada, France, Italy, Spain, UK and US. They found that most agreed with the principle that allocation be based on need and were in favour of donation, while allocation based on the country in which vaccines were developed was least popular.…”
Section: Introductionmentioning
confidence: 99%